Pemanfaatan Geographic Information System (GIS) Pada Pemetaan Agrowisata Jeruk di Kabupaten Garut - Abdul, Muzaki; Rahayu, Sri (Institut Teknologi Garut, 2025)
The agricultural sector, especially citrus, plays an important role in the economy, including through agrotourism that combines tourism and citrus plantations. This agrotourism provides visitors with direct experience of agriculture while also being a place of recreation. Geographic Information System (GIS) is a system that integrates maps, location data, regions, climate, topography, and satellite imagery to manage, analyze, and visualize data. Based on data from the Tourism Office, the number of citrus agrotourism tourists in Garut increases every year thanks to the development of facilities and promotions. However, the obstacle faced is the difficulty of access to the agrotourism location, which is located in a rural area with routes that are not always accurate on maps such as Google Maps. Therefore, this study aims to develop a web-based GIS system using Leaflet JS to map the location of citrus agrotourism. This study uses the Rational Unified Process (RUP) method with the stages of Inception, Elaboration, Construction, and Transition. System modeling is carried out using the Unified Modeling Language (UML), including Use Case Diagrams, Activity Diagrams, Sequence Diagrams, and Class Diagrams. The results of this study are the creation of a GIS system that maps citrus agrotourism in Garut Regency. This system makes it easier for the Tourism Office to report data and helps agrotourism owners to promote their agrotourism locations.